Analyzing medical check-up unit performance through the 7Ps marketing mix framework in a private hospital setting - Sigalingging, Grace Nadya Lusyana; Nurfikri, Ari (Environmental, Social, Governance and Sustainable Business, 2025)
Background: Medistra Hospital's Medical Check-Up (MCU) Unit plays a crucial role in supporting patient health monitoring and hospital revenue. However, the MCU unit failed to meet its annual Key Performance Indicator (KPI) target of a 40% increase in patient visits, achieving only 19.7% in 2023. This study explores the marketing mix factors (7Ps) influencing the underachievement of MCU targets. Methods: A qualitative method was used through structured interviews with three key informants: two MCU administrative staff and one marketing staff. Data were collected during a four-month internship period in 2024. Interview questions were structured around the 7Ps marketing mix framework: Product, Price, Promotion, Place, People, Process, and Physical Facilities. Findings: The study found several factors contributing to KPI underachievement: limited service offerings (e.g., absence of PET scan), price competitiveness against peer hospitals, incomplete one-stop service process, lack of promotional materials and coordination, restricted doctor schedules, technical issues in the registration system, and suboptimal locker room placement. Despite an increase in patient numbers from 1,123 in 2022 to 1,344 in 2023, the growth was insufficient to meet targets. Conclusion: Enhancing service availability, system reliability, targeted promotions, flexible scheduling, and integrated service delivery are crucial for improving MCU performance. Strategic adjustments to the marketing mix can better align services with patient expectations and increase satisfaction, leading to KPI improvement. Novelty/Originality of this article: This study uniquely analyzes hospital medical check-up performance through a comprehensive 7Ps marketing mix framework, offering detailed qualitative insights from operational-level staff. It provides practical recommendations tailored to private hospital settings with similar organizational structures and market segments.